Is calcium a concern in neonates undergoing phototherapy? - Sridhar, N. L.; S., Sreeram; Srinivas, Madoori (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal hypocalcemia is defined as total serum calcium concentration of < 7 mg/dl or ionized calcium concentration of <4 mg/dl (<1 mmol/L). The current aim was to look the effect of phototherapy on ionized calcium levels before and after phototherapy in otherwise healthy term and late preterm (35 to 37 weeks) neonates. Methods: The study group included 50 neonates. Measurement of serum ionized calcium levels was done before and at the end of phototherapy. Results: At the end of phototherapy in study group, a significant fall in calcium level in 64% of term and 76% of late preterm neonates was observed, but almost all except one remained asymptomatic. Conclusions: The efficacy of phototherapy in the prevention and treatment of hyperbilirubinemia in newborn infants has been well established. The mean duration of phototherapy in our study was 32 hours. Duration of phototherapy may influence the severity of hypocalcaemia. The regulation of calcium homeostasis in the newborn period has been of considerable interest. Phototherapy increases calcium absorption by the bones and leads to the reduction of melatonin levels. Changes in melatonin levels affect the incidence of hypocalcaemia-induced phototherapy. The mechanism of hypocalcaemia effect of phototherapy was reported by inhibition of pineal gland via transcranial illumination, resulting to decline of melatonin secretion; which blocks the effect of cortisol on bone calcium. It is suggested that serum calcium levels be assessed in neonates treated with phototherapy. Neonatal Jaundice is one of the most common problems that can occur in the newborn. Hypocalcaemia during phototherapy has been reported in literature.